Smart Campus Framework for Higher Education Institutions in Tanzania - Alex Frank Mongi (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
The deployment of smart campus has gained significance globally as Higher Education Institutions (HEIs) strive to  adopt digital technologies for efficient delivery of education and resource management. In achieveing proper deployment, scholars have proposed various features and frameworks for a smart campus of HEIs. However, HEIs around the globe have different needs and priority depending on their context. Establish a context based framework and features, this study examines smart campus features and their applicability in Tanzanian HEIs. It has adopted a trianglation of Systematic Literature Review (SLR) and Survey methods. Through SLR, the study identified 11 key features that various literature associate them with smart campus. Furthermore, though survey method, the study collected opinions from HEIs in Tanzania to test the findings of results that were obtained from SLR. Through ordinal logistic regression, we found that network infrastructure, smart governance, smart people, smart economy, smart living, and smart technology were more likely agreed as significant features of smart campus (p < 0.05), followed by smart education features with slightly large p-value (p = 0.057). Features like smart environment and smart buildings were perceived as not significant features of smart campus in most of HEIs (p > 0.05). Based on these findings, this study proposes a framework for smart campus that is relevant for HEIs in Tanzania.